2010
DOI: 10.1177/1066480710370758
|View full text |Cite
|
Sign up to set email alerts
|

The Communication Patterns Questionnaire-Short Form: A Review and Assessment

Abstract: The Communication Patterns Questionnaire-Short Form (CPQ-SF) is an 11-item self-assessment of spouses' perceptions of marital interactions. A cited reference review of the CPQ-SF literature revealed no formal assessment of its psychometric properties and that researchers are imprecise in their use, reporting, and referencing of the assessment. Toward improving the use of the CPQ-SF in research and practice, the factor structure and psychometric properties of this scale were examined with data collected from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 39 publications
(85 reference statements)
2
48
0
15
Order By: Relevance
“…Christensen and Heavey (1990) developed an 11-item condensed version, the Communication Pattern Questionnaire-Short Form (CPQ-SF; see Futris et al, 2010 for a review).There are substantial differences between the CPQ-SF and the PDMS-SF. The instructions for taking the CPQ-SF ask individuals to describe the behaviors between themselves and their partner "when issues or problems arise".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Christensen and Heavey (1990) developed an 11-item condensed version, the Communication Pattern Questionnaire-Short Form (CPQ-SF; see Futris et al, 2010 for a review).There are substantial differences between the CPQ-SF and the PDMS-SF. The instructions for taking the CPQ-SF ask individuals to describe the behaviors between themselves and their partner "when issues or problems arise".…”
Section: Discussionmentioning
confidence: 99%
“…Christensen and Heavey (1990) concluded that the CPQ-SF has a two-factor structure consisting of positive interactions and demand-withdraw. Futris, Campbell, Nielsen, and Burwell (2010) provided a three-factor structure of the CPQ-SF that consisted of the positive interaction factor and a division of the demand-withdraw factor into conflict-engaging behaviors (i.e., criticism-defend) and conflict-avoiding behaviors (i.e., demandwithdraw).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has supported the notion that couples who exhibit demand-withdraw patterns of conflict experience more dissatisfaction in their marriage (e.g., Christensen & Shenk, 1991;Futris et al, 2010;Papp, Kouros, & Cummings, 2009). Schrodt, Witt, and Shimkowski (2014) conducted a meta-analysis of 74 studies that examined the demand-withdraw pattern and relational outcomes.…”
Section: The Demand-withdraw Financial Conflict Message Patternmentioning
confidence: 99%
“…Several studies have consistently demonstrated that constructive conflict messages are positively associated with relational satisfaction, whereas destructive messages are negatively associated with relational satisfaction (e.g., Canary & Cupach, 1988;Canary, Cupach, & Serpe, 2001;Futris et al, 2010;Gottman, 1994;Sillars, 1980). For example, Ting-Toomey (1983) coded 34 marital couples' verbal exchanges of conflict when spouses were engaging in disagreements with each other.…”
Section: Constructive and Destructive Financial Conflict Messagesmentioning
confidence: 99%
See 1 more Smart Citation